Uptake of measles second dose vaccine among children aged 15–35 months at Mettu Woreda, Illu Aba Bor Zone, Ethiopia: A community-based cross-sectional study - Alemayehu Workiye Haile; Ebissa Bayana Kebede; Vinod Bagilkar; Teklu Wosenyeleh Mamo; Maycas Gembe (PLoS ONE, 2026)
Background Measles remains a significant global health threat, especially for Children. Its prevention can be achieved through a safe and affordable vaccine. However, there is a paucity of information about the uptake of the measles second-dose vaccine and associated factors in Ethiopia, particularly in Mettu Woreda. Furthermore, this study examined understudied variable maternal trust in healthcare workers. Objectives To assess uptake of measles second dose vaccine and associated factors among children aged 15–35 months at Mettu woreda, Illu Aba bor zone, 2024. Methods A community-based cross-sectional study was conducted from May to June of 2024 among 458 mothers/caregivers with Children aged 15–35 months using a systematic sampling technique. Data was collected using interviews, administered questionnaires. The Statistical Package for the Social Sciences software version 27 was used to analyze the data. Binary logistic regression was used to identify factors associated with the uptake of measles second dose vaccine at P-value < 0.05. Results Coverage of the measles second dose vaccine was 58.5% (95% CI: 53.8–63.1). Factors positively associated with the uptake include maternal age (26−30 [AOR: 2.7, 95% CI (1.46–5.05)], 31−35 [AOR: 3.3, 95% CI (1.52–7.13)]), education; primary([AOR: 3.1, 95% CI (1.35–7.26)], secondary[AOR: 4.3, 95% CI (2.03–9.30)]), knowledge[AOR: 2, 95% CI (1.11–3.64)], information about MCV2[AOR: 3.7, 95% CI (2.10–6.56)], waiting time[AOR: 3, 95% CI (1.45–6.17)], while availability of vaccination service[AOR: 0.4, 95% CI (0.24–0.78)], and lack of trust in health workers[AOR: 0.3, 95% CI (0.18–0.55)] negatively affected vaccine uptake. Conclusion The uptake of the measles second-dose vaccine among children aged 15–35 months is below district and national targets. Maternal age, education, knowledge, information access, trust in healthcare workers, antenatal care, waiting times, and service availability were all associated. Improved community awareness and addressing healthcare facility closures are needed.